Electrochromic semiconductors as colorimetric SERS substrates with high reproducibility and renewability - Shan Cong; Zhen Wang; Wenbin Gong; Zhigang Chen; Weibang Lu; John R. Lombardi; Zhigang Zhao (Nature Communications, 2019)
Electrochromic technology has diverse cutting-edge applications, but it has never been used to overcome the critical problems in the field of surface-enhanced Raman scattering (SERS). Here, the authors demonstrate a generic electrochromic strategy for ensuring the reproducibility and renewability of SERS substrates.